Analisa Pengaruh Beban Kerja Terhadap Kinerja Karyawan Di PT. Sumber Alfaria Trijaya Tbk - Ageng Saepudin Kanda S; Nugraha Rhamdani (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to identify the effect of workload on employee performance at PT. Sumber Alfaria Trijaya. This study was carried out by analyzing data from employees at the company. The research results show that workload has a significant influence on employee performance at PT. Sumber Alfaria Trijaya. High workload can cause a decrease in employee performance, while moderate workload can increase employee performance. In this context, management needs to pay attention to factors that can reduce employee workload, such as assigning tasks that are appropriate to their abilities and experience, efficient time management, and increasing support and training from the company. This research provides a better understanding of the relationship between workload and employee performance at PT. Sumber Alfaria Trijaya, and can be a basis for increasing work effectiveness and efficiency in the company